Open Letter to the International Criminal Court Alleging War Crimes and Crimes Against Humanity for Intentional Triggering the February 6, 2023 Earthquake in the Republic of Türkiye - Herndon, J. Marvin; Whiteside, Mark; Baldwin, Ian (Advances in Social Sciences Research Journal, 2023)
In 1968 MacDonald foresaw the possibility that in the future the military might develop the means to trigger earthquakes: “The key to geophysical warfare is the identification of the environmental instabilities to which the addition of a small amount of energy would release vastly greater amounts of energy.” In 1997, U.S. Secretary of Defense William Cohen confirmed military involvement in such activities. In 2002, the 90 deputies of the Russian State Duma warned the United Nations that Americans were experimenting with a new geophysical weapon and demanded an international ban. The United States, Norway and other nations possess electromagnetic “ionosphere heaters” that are capable of triggering earthquakes. On February 6, 2023, a powerful 7.8 magnitude earthquake occurred in southern Turkey near the northern border of Syria, followed by another earthquake and aftershocks that devastated parts of Turkey and Syria, with the death toll reportedly exceeding 55,100, the majority being women and children, many more injuries, and an estimated 1.5 million people made homeless. Real and fake news reports before and immediately following the event, together with scientific facts and circumstances described here, warrant a full, thorough, and complete investigation by the International Criminal Court of our allegations that said February 6, 2023 earthquake was deliberately triggered and constitutes war crimes and crimes against humanity.